Protein: how much do runners need? - Crowther, G. (2000)
Author answers the question: Do runners need more of dietary protein than couch potatoes? If so, how much more? With special regards to women. A runner's body needs extra protein. But this doesn't mean that he/she needs to stock up on mammoth steaks and giant tubs of tofu. As a runner, you likely eat more than your sedentary sidekicks -- and that means that you likely take in more protein than they do. As long as you consume enough calories to maintain your body weight, and as long as at least 15% of those calories come from protein, you're probably meeting your daily protein needs. (This article originally appeared in the May 2000 issue of Northwest Runner magazine.)